THE ASEAN ECONOMIC COMMUNITY IMPLEMENTATION ASEAN HIGHER EDUCATION SECTORS : AN ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN PRIVATE BUSINESS SCHOOLS - Baskoro, Gading; Sucento, Bun; Pasasa, Linus (Academic Research Centre Services, 2013)
The primary purpose of this research is to identify the competitiveness position of Indonesian private business schools in the ASEAN region in facing ASEAN Economic Community in 2015. This research also tries to identify strategies for Indonesian private business schools in facing the era of ASEAN Economic Community. SWOT analysis is used as the base of this research. AACB's accreditation standards are use for determining factors driven the most to the competitiveness of Indonesian private business schools, while five factors of students' choice  are used to determine the strongest factor that influence ASEAN students' business school choice. Questionaires were distributed to Indonesian private business schools' lecturers and business school students in ASEAN region. After the data was gathered, AMOS Software is used to provide Structural Equation Modeling (SEM) and Path Diagram. Results from this study shows that Indonesian private business schools are in the Cell 3 of SWOT analysis diagram.